2005
DOI: 10.1086/430113
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Quasar Broad Absorption Line Geometry: X-Ray Observations and Two-dimensional Optical Spectroscopy

Abstract: A new generation of sensitive X-ray measurements are indicating that the existence of X-ray attenuation column densities, , is quite common among broad absorption line quasars (BALQSOs). This is significant 24 Ϫ2 N 1 10 cm H to the geometry of the broad absorption line (BAL) outflow. In particular, such an X-ray shield also shields equatorial accretion disk winds from the UV, thereby preventing high-velocity equatorial outflows from being launched. By contrast, bipolar winds initiated by continuum radiation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Specifically, these two models predict some very simple and clear effects (see for a discussion of this point Murray et al 1995; Punsly 1999a,b; Proga, Stone & Kallman 2000a; Punsly & Lípari 2005). Here, we present a summary of the most clear prediction of these two AGN models.…”
Section: Discussion Of the Gmos–ifu Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, these two models predict some very simple and clear effects (see for a discussion of this point Murray et al 1995; Punsly 1999a,b; Proga, Stone & Kallman 2000a; Punsly & Lípari 2005). Here, we present a summary of the most clear prediction of these two AGN models.…”
Section: Discussion Of the Gmos–ifu Resultsmentioning
confidence: 94%
“… To study BALs associated with composite QSOs: AGN + starburst (with jet + accretions discs, shells). Specifically, to study in detail our finding that some BALs systems are linked with: (1) bipolar OF probably generated by subrelativistic jets (Lípari et al 2005; Punsly & Lípari 2005) and (2) supergiant explosive events, probably associated with hypernovae (Lípari et al 2005). Our purpose is to study the spatial distribution, and the kinematics and physical properties of the ionized gas, stars and dust, all of which provide information about the evolutionary conditions of the interstellar medium (ISM) and the possible origins of extreme star formation and explosive processes. To investigate the presence, properties, origin and importance of GWs, stellar populations and giant explosions in BAL + IR + Fe ii QSOs/mergers.In particular, it is important to study in detail the host galaxies of BAL + IR QSOs, specially the presence of GWs, young stellar populations [with Wolf–Rayet (WR) features, etc.…”
Section: Gemini Programme Of Bal Qsosmentioning
confidence: 99%
See 1 more Smart Citation
“…In objects with L/L Edd P 0:2%-1%, the wind becomes equatorial or cannot fully develop. The possible existence of bipolar disk winds in quasars was explored by Punsly & Lipari (2005), and in the nearest BAL quasar, Mrk 231, evidence has been found that the BAL outflow is parallel to the parsec-scale radio jet. Reichard et al (2003b) found an uncorrected fraction of 14:0% AE 1:0% of BAL quasars in the SDSS EDR within the redshift range 1:7 z 3:4, whereas Menou et al (2001) found that this fraction falls to 3:3% AE 1:1% among those quasars with FIRST detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent numerical work ini ∼ 60Њ dicates that it is also plausible to launch bipolar outflows from the inner regions of a thin disk (e.g., Punsly 1999; Proga & Kallman 2004). There is growing observational evidence indicating the existence of polar BAL outflows (e.g., Punsly & Lipari 2005;Ghosh & Punsly 2007;Zhou et al 2006;Becker et al 2000; Barvainis & Lonsdale 1997;Jiang & Wang 2003).…”
Section: Introductionmentioning
confidence: 99%